INTEGRASI BIM-IOT DALAM KONSTRUKSI INDONESIA: ANALISIS STUDI KASUS KOMPARATIF - Mahatama, I Kadek Badradnyana Wirapraja; Sanjaya, I Putu Ari (Jurnal Spektran, 2026)
Building Information Modeling (BIM) has become a global standard in the construction industry, delivering 30–50% efficiency improvements and significant cost reductions. However, Indonesia faces an adoption paradox where high awareness levels (67–72%) contrast sharply with low implementation rates (38%), creating a persistent gap of approximately 30 percentage points despite regulatory mandates introduced since 2018. This systematic literature review aims to assess BIM maturity levels in Indonesia, identify Technology–Organization–Environment (TOE) factors influencing BIM–IoT integration readiness, determine the minimum BIM maturity threshold required for Digital Twin integration, and evaluate maturity assessment frameworks applicable to the Indonesian context. Following PRISMA 2020 guidelines, 123 peer-reviewed studies (41.5% from Q1 journals) published between 2013–2025 were analyzed using the TOE framework combined with Succar's BIM Maturity Matrix. The findings indicate that BIM maturity in Indonesia remains predominantly at Level 1 (38.2%), with only 11.8% achieving Level 2, while across 527 TOE factor occurrences, barriers (61.1%) significantly outweighed enablers (38.9%), with human resources and skills limitations emerging as the most frequently cited barrier. BIM–Digital Twin integration, which dominates global research trajectories, requires at least Level 2 maturity, a threshold not yet reached by most Indonesian organizations. Furthermore, only two Indonesia-specific assessment frameworks were identified, i.e. highlighting the need for a dual strategy combining top-down regulatory enforcement with bottom-up capacity development to accelerate BIM–IoT integration readiness in Indonesia.